Fabrication of custom overdenture attachments using indigenously made parallelometer: A technique - Ravindra S Pawar; Pravin E Raipure; Rahul S Kulkarni; Mohana Tagore; Raguram Ganesan (Wolters Kluwer Medknow Publications, 2019)
Various types of attachments have been used during overdenture fabrication; however, no single attachment is perfect for every case. Irrespective of the attachment used, it is important to maintain parallelism between the attachments for ease of insertion and removal, functional efficiency, and durability of the prosthesis. It is challenging to obtain parallelism between attachments when the abutments are divergent, or multiple abutments are engaged. A simplified technique to fabricate cast overdenture attachments using indigenously made parallelometer has been described. This technique eliminates the need of making full-arch impressions and models and surveying the attachments before casting. With this technique, there is a reduction in the duration and cost of treatment, without any compromise in quality of the prosthesis.